2013
DOI: 10.1111/bph.12450
|View full text |Cite
|
Sign up to set email alerts
|

The Concise Guide toPHARMACOLOGY2013/14: Transporters

Abstract: The Concise Guide to PHARMACOLOGY 2013/14 provides concise overviews of the key properties of over 2000 human drug targets with their pharmacology, plus links to an open access knowledgebase of drug targets and their ligands (www.guidetopharmacology.org), which provides more detailed views of target and ligand properties. The full contents can be found at http://onlinelibrary.wiley.com/doi/10.1111/bph.12444/full.Transporters are one of the seven major pharmacological targets into which the Guide is divided, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(73 citation statements)
references
References 672 publications
(409 reference statements)
1
70
0
2
Order By: Relevance
“…The 11 C-sarcosine uptake was determined to be 12.5% 6 1.1% of the administered dose (n 5 12). 11 C-sarcosine uptake was then determined using specific competitive inhibitors of 2 amino acid transporter systems, 5-hydroxy-L-tryptophan (HT) for the protoncoupled amino acid transporters (PAT1 gene symbol SLC36A1, PAT2 gene symbol SLC36A2, PAT4 gene symbol SLC36A4) (15) and 2-aminobicyclo-(2,2,1)-heptane-2-carboxylic acid (BCH) for system L (16). Thereafter, 11 C-sarcosine was added to cells for 20 min and washed 3 times before counting.…”
Section: C-sarcosine Cell Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The 11 C-sarcosine uptake was determined to be 12.5% 6 1.1% of the administered dose (n 5 12). 11 C-sarcosine uptake was then determined using specific competitive inhibitors of 2 amino acid transporter systems, 5-hydroxy-L-tryptophan (HT) for the protoncoupled amino acid transporters (PAT1 gene symbol SLC36A1, PAT2 gene symbol SLC36A2, PAT4 gene symbol SLC36A4) (15) and 2-aminobicyclo-(2,2,1)-heptane-2-carboxylic acid (BCH) for system L (16). Thereafter, 11 C-sarcosine was added to cells for 20 min and washed 3 times before counting.…”
Section: C-sarcosine Cell Assaysmentioning
confidence: 99%
“…Briefly, the organ distribution of 11 C-sarcosine was determined in 2 male and 2 female Sprague-Dawley rats at 5 time points (5,15,30,60, and 90 min) using injected doses of 7.4-28 MBq of 11 C-sarcosine. Groups of animals were sacrificed while under isoflurane anesthesia.…”
Section: C-sarcosine Biodistributionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS1 encodes a protein involved in G protein signaling (Kim et al, 2010). A number of important receptors in the pituitary gland are G protein coupled receptors (Alexander et al, 2013), and further investigations should look into whether the RGS1 protein interacts with the functioning of these, and if this is affected by stress exposure.…”
Section: The Avian Stress Responsementioning
confidence: 99%
“…Interestingly, both mechanical stress and hypertrophic stimuli (Ang II, endothelin-1) activated volume-regulated Cl − currents in cardiomyocytes and vascular smooth muscle cells (VSMCs; Sato and Koumi, 1998;Shi et al, 2007;Ren et al, 2008). Our previous studies demonstrated that ClC-3 (see Alexander et al, 2013) is responsible for volume-regulated Cl − currents in VSMCs (Zhou et al, 2005) and the activity of the volumeregulated ClC-3 Cl − channel displayed a pressure-dependent increase in basilar artery smooth muscle cells (BASMCs) from 2-kidney 2-clip (2K2C) hypertensive rats, and the size of this increase paralleled the severity of cerebrovascular remodelling (Shi et al, 2007). Also, a deficiency of ClC-3 channels attenuated cerebrovascular remodelling during hypertension (Liu et al, 2010;Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%